1975
DOI: 10.1017/s0022172400024396
|View full text |Cite
|
Sign up to set email alerts
|

Serologic evidence of the postoperative persistence of hydatid cysts in man

Abstract: SUMMARYThe sensitivity of the haemagglutination, complement-fixation and indirect fluorescent antibody tests in the diagnosis of primary and recurrent hydatid disease is presented. In the first, diagnostic titres were obtained in 90%, 80 % and 96% of 50 patients with hepatic and 64%, 60% and 68% of 25 patients with pulmonary cysts, respectively. In the postoperative study of 62 patients, elevated titres of HA, CF and IFA antibodies in 30 led to the presumptive diagnosis of recurrent disease, confirmed later by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…These findings are in line with observations by Roy et al [15] who discovered that complement fixation test yields negative results two months to one year after surgery and Matossian and Araj [16] who demonstrated that complement fixing antibodies were not detected in 72% of the patients with hydatidosis, a year or more after the operation. Todorov and Stojanov [17] reported that serological test for hydatid disease either becomes negative six months to two years after surgical removal of the cysts or remained positive for more than four years (the entire period of the study).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in line with observations by Roy et al [15] who discovered that complement fixation test yields negative results two months to one year after surgery and Matossian and Araj [16] who demonstrated that complement fixing antibodies were not detected in 72% of the patients with hydatidosis, a year or more after the operation. Todorov and Stojanov [17] reported that serological test for hydatid disease either becomes negative six months to two years after surgical removal of the cysts or remained positive for more than four years (the entire period of the study).…”
Section: Discussionsupporting
confidence: 91%
“…Seven out of 9 of these had a pattern of rising CFA initially, and later falls correlating with clinical and radiological improvement (patients 1,5,7,12,14,15,16). Antibody titres increased at least 4 times in all except one (patient 15), and the rise occurred either during or within 3 months of the end of chemotherapy.…”
Section: Introductionmentioning
confidence: 96%
“…To analyse the serology data four groups ofpatients were identified, according to treatment by surgery and/or albendazole, and whether or not relapse occurred (Figures 1-4 1,5,6,7,9,11,14) Patients 1,5,7,14 received albendazole before surgery and all had similar patterns of CFT results (Figure 1). A 4-fold or greater rise in complement fiing antibodies (CFA) occurred during or within 3 months of the end of chemotherapy and was followed by subsequent fall.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, surgery was the only way of treating hydatid disease. Despite adequate surgery 10 to 15 per cent of patients fail to recover owing to the inaccessibility of their lesions or chronic host tissue reactions [1,2]. In recent years surg ica l excision of cysts combined with effective doses of albendazole has given encouraging results in the treatment of chronic multi focal abdominal hydatidosis.…”
mentioning
confidence: 99%